El Marketing Educativo y la percepción de calidad de servicio en la Escuela Académico Profesional de Economía-UNT-2017 - Oliva Zelada, Heber Celso (2018)
ABSTRACT The central aim of this thesis was to study the relationship between Educational Marketing and the Perception of Service Quality in the Academic Professional School of Economics of the National University of Trujillo-2017. It was an explanatory and correlational study that used the inductive-quantitative method with a randomized sample of 233 students from a population of 593 students enrolled in the School of Economics-UNT-2017, who answered a questionnaire on Likert scale, previously validated and reliabilized. The educational marketing and its dimensions: Product, Promotion and education, Personnel, process and physical environment, has been considered as optimal by more than half (59.7%) of the students surveyed in EAP of Economics of the UNT-2017. Likewise, the quality of service and its dimensions: tangible elements, reliability, responsiveness, security and empathy, has been perceived as adequate by a majority of 64.38% of the students surveyed in the Economics EAP of the UNT-2017. Finally, the estimation results of the relationship between the variables, through the Spearman's Rho statistic, account for the existence of a correlation rs = 0. 848, so it can be affirmed that there is a positive significant relationship between the variables educational marketing and perception of quality of service of the students of the EAP of Economy of the UNT-2017.